We are a college at war : women working for victory in World War II - Weaks-Baxter, Mary (Southern Illinois University Press, 2010)
We Are a College at War weaves together the World War II experiences of students and faculty at Rockford College in Rockford, Illinois, to provide readers with a better understanding of the role American women and college students played during this defining period in U.S. history. Drawing on the Rockford community's letters, speeches, and campus newspaper archives, the authors demonstrate how women claimed the right to be everywhere-in factories and other traditionally male workplaces, and even on the front lines-and link their efforts to the rise of feminism and the fight fo.